Identification of Potential Locations for Soil Investigation based On Geographic Information System (GIS) - Apriani, Dyah Wahyu; Qusairy, Muhammad Ichsan (Universitas Negeri Semarang, 2024)
A site study is conducted to comprehend the stratigraphy, soil type, water depth, and soil deformation qualities. Using this data, cost-effective substructure designs, supporting structure research, alternative development plans, and the site's safety are all possible. Site investigations must be planned to obtain maximum information, represent field soil conditions, and be relevant to development. Excessive investigations waste money and time, while insufficient investigations raise the risk of failure of the constructed structures and cause the data not to reflect the area's conditions accurately. Planners can determine where a site investigation should be conducted in each area by mapping possible investigation locations. The Standard Penetration Test and Cone Penetration Test site investigation location data are used in this study to map possible site investigation locations using spatial analysis in GIS, yielding recommended investigation locations. Elevation, slope, and prior site studies are the three parameters combined to create the weighting method, fuzzy overlay gamma, and per-cell statistical maximum employed in the spatial analysis. The inference matrix is used to validate the accuracy of the spatial analysis results. The inference matrix validation results indicate that the weighting approach has a higher accuracy rate of 63,55%. The findings indicated that the southeast, northeast, and west of the research site had significant potential for site studies in limited regions